Preparation method of amino-functionalized UiO-66 supported platinum-cobalt bimetallic nano-alloy catalyst
By directly synthesizing UiO-66-NH2-supported platinum-cobalt bimetallic nanoalloy catalysts with cobalt oxide during the solvent heat process, the problem of insufficient performance of the catalyst prepared by selective hydrogenation of α,β-unsaturated aldehydes in the prior art was solved, and efficient preparation of the catalyst and excellent catalytic performance were achieved.
Patent Information
- Application Number
- CN202310682428.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-09
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-06-09
AI Technical Summary
In the prior art, the catalyst performance of α,β-unsaturated alcohols is insufficient by selective hydrogenation of α,β-unsaturated aldehyde, especially the adsorption and conversion ability of C=O bonds, resulting in low selectivity and efficiency.
An amino-functionalized UiO-66-supported platinum-cobalt bimetallic nanoalloy catalyst was prepared by using cobalt oxide as the cobalt source during the solvent heat process, and the MOFs (UiO-66-NH2)-supported platinum-cobalt bimetallic catalyst was directly synthesized by using cobalt oxide as a cobalt source during the solvent heat process to form PtCo alloy and Co-NxLewis acid sites, which jointly improve catalytic activity and selectivity.
The efficient preparation of the catalyst was achieved, the regular morphology and good crystallinity of UiO-66-NH2 were maintained, and the catalytic performance was improved, especially in the hydrogenation reaction of cinnamaldehyde, the conversion rate and selectivity were significantly improved.
Smart Images

Figure CN116786169B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalytic technology, and in particular to a method for preparing an amino-functionalized UiO-66-loaded platinum-cobalt bimetallic nano-alloy catalyst. Background Art
[0002] α,β-unsaturated aldehyde molecules contain C=C and C=O double bonds, such as butenal, cinnamaldehyde, furfural, citral, citronellal, etc. The C=O bond selective hydrogenation product - α,β-unsaturated alcohol, has a wide range of important applications in the pharmaceutical, fragrance and other fine chemical industries. However, due to the C=O double bond (bond energy 715 kJ·mol -1 ) is thermodynamically stronger than a C=C double bond (bond energy 615 kJ·mol -1 ) is more stable, and it is difficult to obtain unsaturated alcohols with high selectivity. The heterogeneous catalytic selective hydrogenation method using H2 as the hydrogen source is considered to have the potential to replace the traditional industrial reduction method of unsaturated aldehydes using NaBH4 and LiAlH4, which are difficult to separate, environmentally polluting and costly.
[0003] At present, the catalysts used for the selective hydrogenation of α,β-unsaturated aldehydes to prepare α,β-unsaturated alcohols are mainly based on precious metal catalysts such as Pt, Ir, and Ru. In order to improve the selectivity of unsaturated alcohol products and enhance the adsorption and conversion capacity of C=O bonds, the catalysts are often regulated in the following three ways: (1) Selecting a suitable carrier and using the interaction between the active component and the carrier to change the dispersion and state of the active component to facilitate the adsorption and activation of the C=O bond (G. Kennedy et al, In Situ Spectroscopic Investigation into the Active Sites for Crotonaldehyde Hydrogenation at the Pt Nanoparticle–Co3O4 Interface, ACS Catal, 2016, 6: 7140-7147.). (2) Adding additives to regulate the electronic structure of the active component. Metals or metal oxides such as Fe, Sn, and Co all have certain additive effects and have different electronic regulation effects on platinum active metals. Among them, platinum-cobalt bimetallic catalysts have received great attention. For example, patent CN105148939A discloses a highly dispersed supported PtCo nano-alloy catalyst with high selectivity for cinnamyl alcohol; Pt in the PtCo bimetallic catalyst δ- -Co δ+The site is conducive to the adsorption of C=O bonds, thereby improving the selectivity of C=O hydrogenation (X. Wang et al, Atomic layer deposited Pt-Co bimetallic catalystsfor selective hydrogenation of α,β-unsaturated aldehydes tounsaturatedalcohols, J. Catal, 2018, 366: 61-69.). (3) Use steric hindrance to regulate selectivity. Metal-organic framework materials (MOFs) have unique pore structure characteristics. When active metals such as platinum are confined in the cavity, it provides a limiting effect for the reactant molecules to selectively contact the active sites. For example, platinum nanoparticles are confined in UiO-66-NH2, showing a higher selectivity for cinnamaldehyde (Z. Guo et al, Pt Nanoclusters Confined within Metal–Organic Framework Cavities for Chemoselective Cinnamaldehyde Hydrogenation, ACS Catal, 2014, 4: 1340-1348).
[0004] In recent years, researchers have tried to combine the above-mentioned effects to further synergistically improve the performance of catalysts. However, the composite materials formed by encapsulating metal alloys or metal oxides into MOFs usually face the problem of multi-step and complex preparation processes. For example, a step-by-step impregnation method is used to load platinum and a second metal into the MOFs pores to obtain a bimetallic alloy catalyst (B. Zhang et al, Influence of Sn on Stability and Selectivity of Pt–Sn@UiO-66-NH2in Furfural Hydrogenation, Ind. Eng. Chem. Res, 2020, 59: 17495-17501). Alternatively, metal or metal oxide nanoparticles are synthesized first, and then MOFs are grown in situ (Y. Long et al, Pt / CeO2@MOFCore@Shell Nanoreactor forSelective Hydrogenation of Furfural via the ChannelScreening Effect, ACS Catal, 2018, 8: 8506-8512). When a one-pot method is used to prepare bimetallic alloy catalysts, the MOFs morphology is often lost (J.Cao et al, One-step synthesis of Co-doped UiO-66 nanoparticle with enhanced removal efficiency of tetracycline: Simultaneous adsorption and photocatalysis, Chem. Eng. J, 2018, 353: 126–137). Therefore, based on these problems, it is necessary to develop a simple and effective method to prepare MOFs-supported Pt-based bimetallic nanoalloy composite catalysts to more efficiently catalyze the selective hydrogenation of unsaturated aldehydes. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing an amino-functionalized UiO-66-loaded platinum-cobalt bimetallic nano-alloy catalyst which has a simple preparation method and high selective hydrogenation activity.
[0006] In order to solve the above problems, the preparation method of the amino-functionalized UiO-66 supported platinum-cobalt bimetallic nano-alloy catalyst of the present invention comprises the following steps:
[0007] (1) Dissolving platinum salt and 2-aminoterephthalic acid in N,N-dimethylformamide solvent to form a platinum-containing solution; the molar volume ratio of the platinum salt to the N,N-dimethylformamide is 1:793; the concentration of the 2-aminoterephthalic acid in the N,N-dimethylformamide is 20 mmol / L;
[0008] (2) adding acetic acid to the platinum-containing solution and stirring evenly to obtain an acidified platinum solution; the volume ratio of the acetic acid to the N,N-dimethylformamide is 4:23;
[0009] ⑶ Dissolve the zirconium salt in N,N-dimethylformamide solvent to obtain a mixed solution, add cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 5 to 30 minutes to obtain a cobalt-containing suspension; the concentration of the zirconium salt in the N,N-dimethylformamide is 80 mmol / L; the mass volume ratio of the cobalt oxide to the mixed solution is 2 to 14:1;
[0010] (4) mixing the acidified platinum solution with the cobalt-containing suspension, and transferring the mixture to a reactor with a polytetrafluoroethylene liner for heating reaction to obtain a mixed solution;
[0011] (5) The mixed solution is centrifuged, washed and dried to obtain a light brown solid product;
[0012] (6) The solid product is reduced in a hydrogen / nitrogen mixed atmosphere to obtain an amino-functionalized UiO-66-loaded platinum-cobalt bimetallic nanoalloy catalyst (PtCo@UiO-66-NH2).
[0013] The platinum salt in step (1) refers to one of chloroplatinic acid, platinum ammonia chloride and platinum ammonia nitrate.
[0014] In step (3), the zirconium salt refers to zirconium tetrachloride or zirconium nitrate.
[0015] In step (3), the cobalt oxide refers to divalent cobalt oxide, i.e., CoO, and the atomic ratio of cobalt to platinum is 0.15 to 1.1.
[0016] The heating reaction conditions in step (4) are a temperature of 120° C. and a time of 12 to 36 h.
[0017] The washing conditions in step (5) refer to washing with N,N-dimethylformamide and methanol 3 to 4 times respectively.
[0018] The drying conditions in step (5) are a temperature of 80°C and a time of 6 to 12 hours.
[0019] In the step (6), the volume fraction of hydrogen in the hydrogen / nitrogen mixed gas is 10 vol%.
[0020] The reduction treatment conditions in step (6) refer to a reduction temperature of 200-250°C and a reduction time of 1-3 h.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. The present invention uses cobalt oxide (CoO) as a cobalt source to directly synthesize a platinum-cobalt bimetallic alloy catalyst supported by MOFs (UiO-66-NH2) by a one-pot method. During the solvothermal process, CoO slowly dissolves and releases Co in situ. 2+ , which has a strong interaction with Pt, is conducive to the formation of PtCo alloy. At the same time, part of Co coordinates with amino groups to form Co-N x sites without affecting the growth of UiO-66-NH2, and finally a PtCo bimetallic nanoalloy composite catalytic material with good crystallinity, UiO-66-NH2 morphology and large specific surface area can be obtained.
[0023] 2. The catalyst prepared by the present invention not only maintains the regular morphology and good crystallinity of UiO-66-NH2, but also has Pt nanoparticles, PtCo alloy and Co-N x Lewis acid sites, this multi-active site synergistic effect promotes the activity and selectivity of the catalyst.
[0024] 3. The present invention uses a very small amount of Co to significantly improve the catalytic performance, greatly saving resources and improving utilization.
[0025] 4. Compared with other similar products, the preparation method of the present invention is simple and has fewer steps. The obtained catalyst has the characteristics of good dispersion of active components, high utilization rate, regular structure, etc., which can effectively solve the problems of low C=O bond adsorption and conversion capacity in the hydrogenation of α,β-unsaturated aldehydes to unsaturated alcohols in the prior art.
[0026] 5. The electronic state of Pt in the catalyst prepared by the present invention is better regulated, which can significantly inhibit the adsorption of C=C bonds and improve the selectivity of C=O bond hydrogenation. When used for cinnamaldehyde hydrogenation, the conversion rate of cinnamaldehyde and the selectivity of cinnamyl alcohol can reach 93% and 94% respectively at 70°C and 2MPa, and the yield of cinnamyl alcohol can be close to 5000 mmol·g Pt -1 ·h -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0028] Figure 1XRD patterns of the PtCo@UiO-66-NH2 bimetallic nanoalloy catalyst obtained in Examples 1 to 4 of the present invention, the Pt@UiO-66-NH2 catalyst obtained in Comparative Example 1, and the PtCo(A)@UiO-66-NH2 catalyst obtained in Comparative Example 2.
[0029] Figure 2 TEM images of the PtCo@UiO-66-NH2 bimetallic nanoalloy catalyst obtained in Examples 1 to 4 of the present invention, the Pt@UiO-66-NH2 catalyst obtained in Comparative Example 1, the PtCo(A)@UiO-66-NH2 catalyst obtained in Comparative Example 2, and the PtCo / UiO-66-NH2 catalyst obtained in Comparative Example 3.
[0030] Figure 3 This is a TEM elemental surface scan of the PtCo@UiO-66-NH2 bimetallic nanoalloy catalyst obtained in Example 4 of the present invention.
[0031] Figure 4 HRTEM images of the PtCo@UiO-66-NH2 bimetallic nanoalloy catalyst obtained in Examples 1 to 4 of the present invention, the Pt@UiO-66-NH2 catalyst obtained in Comparative Example 1, the PtCo(A)@UiO-66-NH2 catalyst obtained in Comparative Example 2, and the PtCo / UiO-66-NH2 catalyst obtained in Comparative Example 3.
[0032] Figure 5 XPS graphs of the PtCo@UiO-66-NH2 bimetallic nanoalloy catalyst obtained in Examples 1 to 4 of the present invention, the PtCo@UiO-66-NH2 catalyst obtained in Comparative Example 1, and the PtCo(A)@UiO-66-NH2 catalyst obtained in Comparative Example 2.
[0033] Figure 6 It is a CO-DRIFTS diagram of the PtCo@UiO-66-NH2 bimetallic nanoalloy catalyst obtained in Examples 1 to 4 of the present invention and the PtCo@UiO-66-NH2 catalyst obtained in Comparative Example 1. DETAILED DESCRIPTION
[0034] The preparation method of amino-functionalized UiO-66 supported platinum-cobalt bimetallic nano alloy catalyst comprises the following steps:
[0035] (1) Dissolve platinum salt and 2-aminoterephthalic acid in N,N-dimethylformamide solvent to form a platinum-containing solution.
[0036] Wherein: platinum salt refers to one of chloroplatinic acid, platinum chloride and platinum nitrate. The molar volume ratio of platinum salt to N,N-dimethylformamide is 1:793; the concentration of 2-aminoterephthalic acid in N,N-dimethylformamide is 20 mmol / L.
[0037] ⑵ Add acetic acid to the platinum-containing solution, with the volume ratio (mL / mL) of acetic acid to N,N-dimethylformamide being 4:23. Stir evenly to obtain an acidified platinum solution.
[0038] ⑶ Dissolve the zirconium salt in N,N-dimethylformamide solvent to obtain a mixed solution, add cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 5 to 30 minutes to obtain a cobalt-containing suspension.
[0039] Wherein: zirconium salt refers to zirconium tetrachloride or zirconium nitrate. Cobalt oxide refers to divalent cobalt oxide, namely CoO, and the atomic ratio of cobalt to platinum is 0.15-1.1.
[0040] The concentration of zirconium salt in N,N-dimethylformamide is 80 mmol / L; the mass volume ratio (g / mL) of cobalt oxide to the mixed solution is 2~14:1.
[0041] (4) Mix the acidified platinum solution and the cobalt-containing suspension, transfer them to a reactor with a polytetrafluoroethylene liner, heat them at 120 °C for 12 to 36 h, and take out the mixed solution after the reaction after the temperature of the reactor drops to room temperature.
[0042] (5) After centrifugation, the mixed solution was washed with N,N-dimethylformamide and methanol for 3 to 4 times respectively, and then dried at 80 °C for 6 to 12 h to obtain a light brown solid product.
[0043] (6) The solid product was reduced in a hydrogen / nitrogen mixed atmosphere at 200-250 °C for 1-3 h, wherein the volume fraction of hydrogen in the hydrogen / nitrogen mixed gas was 10 vol%. After the treatment, amino-functionalized UiO-66-loaded platinum-cobalt bimetallic nanoalloy catalyst (PtCo@UiO-66-NH2) was obtained.
[0044] Example 1 A method for preparing a PtCo@UiO-66-NH2 nano alloy catalyst comprises the following steps:
[0045] (1) Dissolve 15 mg of chloroplatinic acid and 87 mg of 2-aminoterephthalic acid in 23 mL of N,N-dimethylformamide solvent to form a platinum-containing solution.
[0046] ⑵ Add 4 mL of acetic acid to the platinum-containing solution and stir evenly to obtain an acidified platinum solution.
[0047] ⑶ Dissolve 112 mg of zirconium tetrachloride in 6 mL of N,N-dimethylformamide solvent to obtain a mixed solution, add 15 mg of cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 30 minutes to obtain a cobalt-containing suspension.
[0048] (4) The acidified platinum solution was mixed with the cobalt-containing suspension and transferred to a reactor with a polytetrafluoroethylene liner, heated at 120 °C for 24 h, and the reaction mixture was taken out after the temperature of the reactor dropped to room temperature.
[0049] (5) After centrifugation, the mixed solution was washed three times with N,N-dimethylformamide and methanol respectively, and then dried at 80 °C for 12 h to obtain a light brown solid product.
[0050] (6) The solid product was reduced at 200°C for 3 h in a 10 vol% hydrogen / nitrogen mixed atmosphere to obtain the catalyst PtCo@UiO-66-NH2. The Co / Pt in the catalyst is 0.15, and the Pt content is 2.0 wt%.
[0051] Example 2 A method for preparing a PtCo@UiO-66-NH2 nano alloy catalyst comprises the following steps:
[0052] (1) Dissolve 11 mg of platinum nitrate and 87 mg of 2-aminoterephthalic acid in 23 mL of N,N-dimethylformamide solvent to form a platinum-containing solution.
[0053] ⑵ Add 4 mL of acetic acid to the platinum-containing solution and stir evenly to obtain an acidified platinum solution.
[0054] (3) Dissolve 163 mg of zirconium nitrate in 6 mL of N,N-dimethylformamide solvent to obtain a mixed solution, add 40 mg of cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 30 minutes to obtain a cobalt-containing suspension.
[0055] (4) The acidified platinum solution was mixed with the cobalt-containing suspension and transferred to a reactor with a polytetrafluoroethylene liner, heated at 120 °C for 30 h, and the reaction mixture was taken out after the temperature of the reactor dropped to room temperature.
[0056] (5) After centrifugation, the mixed solution was washed four times with N,N-dimethylformamide and methanol respectively, and then dried at 80 °C for 10 h to obtain a light brown solid product.
[0057] (6) The solid product was reduced at 250 °C for 3 h in a 10 vol% hydrogen / nitrogen mixed atmosphere to obtain the catalyst PtCo@UiO-66-NH2. The Co / Pt in the catalyst is 0.27, and the platinum content is 1.9 wt%.
[0058] Example 3 A method for preparing a PtCo@UiO-66-NH2 nano alloy catalyst comprises the following steps:
[0059] (1) Dissolve 10 mg of ammonium platinum chloride and 87 mg of 2-aminoterephthalic acid in 23 mL of N,N-dimethylformamide solvent to form a platinum-containing solution.
[0060] ⑵ Add 4 mL of acetic acid to the platinum-containing solution and stir evenly to obtain an acidified platinum solution.
[0061] ⑶ Dissolve 112 mg of zirconium tetrachloride in 6 mL of N,N-dimethylformamide solvent to obtain a mixed solution, add 56 mg of cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 30 minutes to obtain a cobalt-containing suspension.
[0062] (4) The acidified platinum solution was mixed with the cobalt-containing suspension and transferred to a reactor with a polytetrafluoroethylene liner, heated at 120 °C for 36 h, and the reaction mixture was taken out after the temperature of the reactor dropped to room temperature.
[0063] (5) After centrifugation, the mixed solution was washed four times with N,N-dimethylformamide and methanol respectively, and then dried at 80 °C for 8 h to obtain a light brown solid product.
[0064] (6) The solid product was reduced at 220 °C for 2 h in a 10 vol% hydrogen / nitrogen mixed atmosphere to obtain the catalyst PtCo@UiO-66-NH2. The Co / Pt ratio in the catalyst was 0.41, and the platinum content was 1.9 wt%.
[0065] Example 4 A method for preparing a PtCo@UiO-66-NH2 nano alloy catalyst comprises the following steps:
[0066] (1) Dissolve 15 mg of chloroplatinic acid and 87 mg of 2-aminoterephthalic acid in 23 mL of N,N-dimethylformamide solvent to form a platinum-containing solution.
[0067] ⑵ Add 4 mL of acetic acid to the platinum-containing solution and stir evenly to obtain an acidified platinum solution.
[0068] (3) Dissolve 112 mg of zirconium tetrachloride in 6 mL of N,N-dimethylformamide solvent to obtain a mixed solution, add 68 mg of cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 30 minutes to obtain a cobalt-containing suspension.
[0069] (4) The acidified platinum solution was mixed with the cobalt-containing suspension and transferred to a reactor with a polytetrafluoroethylene liner, heated at 120 °C for 36 h, and the reaction mixture was taken out after the temperature of the reactor dropped to room temperature.
[0070] (5) After centrifugation, the mixed solution was washed four times with N,N-dimethylformamide and methanol respectively, and then dried at 80 °C for 10 h to obtain a light brown solid product.
[0071] (6) The solid product was reduced at 200 °C for 3 h in a 10 vol% hydrogen / nitrogen mixed atmosphere to obtain the catalyst PtCo@UiO-66-NH2. The Co / Pt ratio in the catalyst was 0.80, and the platinum content was 2.1 wt%.
[0072] Example 5 A method for preparing a PtCo@UiO-66-NH2 nano alloy catalyst comprises the following steps:
[0073] (1) Dissolve 15 mg of chloroplatinic acid and 87 mg of 2-aminoterephthalic acid in 23 mL of N,N-dimethylformamide solvent to form a platinum-containing solution.
[0074] ⑵ Add 4 mL of acetic acid to the platinum-containing solution and stir evenly to obtain an acidified platinum solution.
[0075] (3) Dissolve 112 mg of zirconium tetrachloride in 6 mL of N,N-dimethylformamide solvent to obtain a mixed solution, add 80 mg of cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 30 minutes to obtain a cobalt-containing suspension.
[0076] (4) The acidified platinum solution was mixed with the cobalt-containing suspension and transferred to a reactor with a polytetrafluoroethylene liner, heated at 120 °C for 36 h, and the reaction mixture was taken out after the temperature of the reactor dropped to room temperature.
[0077] (5) After centrifugation, the mixed solution was washed four times with N,N-dimethylformamide and methanol respectively, and then dried at 80 °C for 6 h to obtain a light brown solid product.
[0078] (6) The solid product was reduced at 230 °C for 2 h in a 10 vol% hydrogen / nitrogen mixed atmosphere to obtain the catalyst PtCo@UiO-66-NH2. The Co / Pt in the catalyst is 1.07, and the platinum content is 2.1 wt%.
[0079] Comparative Example 1 Preparation of Pt@UiO-66-NH2 Catalyst
[0080] Except for not adding CoO, the rest of the preparation method and dosage were the same as those in Example 1, and the Pt content in the catalyst was 2.0 wt%.
[0081] Comparative Example 2 Preparation of PtCo(A)@UiO-66-NH2 Catalyst
[0082] (1) Dissolve 15 mg of chloroplatinic acid and 87 mg of 2-aminoterephthalic acid in 23 mL of N,N-dimethylformamide solution to form a platinum-containing solution.
[0083] (2) Add 4 mL of acetic acid to the platinum-containing solution and stir evenly to obtain an acidified platinum solution.
[0084] (3) Dissolve 112 mg of zirconium tetrachloride in 6 mL of N,N-dimethylformamide solvent, add 115 mg of cobalt acetate tetrahydrate, and stir for 20 min to obtain a uniform cobalt-containing solution.
[0085] (4) The acidified platinum solution was mixed with the cobalt-containing solution, transferred to a reactor with a polytetrafluoroethylene liner, and reacted at 120 °C for 30 h.
[0086] (5) After the temperature of the reactor dropped to room temperature, the reaction mixture was taken out, centrifuged, washed three times with N,N-dimethylformamide and methanol respectively, and dried at 80 °C for 12 h to obtain a light brown solid product.
[0087] (6) The solid product was reduced in a 10 vol% hydrogen-nitrogen mixture at 200 °C for 3 h to obtain a PtCo(A)@UiO-66-NH2 catalyst with a Co / Pt ratio of 0.1 and a platinum content of 2.1 wt%.
[0088] Comparative Example 3 Preparation of PtCo / UiO-66-NH2 Catalyst
[0089] (1) Disperse 210 mg UiO-66-NH2 in 10 mL deionized water and ultrasonicate for 1 h to form a uniform suspension.
[0090] (2) Add chloroplatinic acid aqueous solution containing 5 mmol / L platinum to the above suspension and stir for 24 h.
[0091] (3) The mixture was centrifuged, washed three times with deionized water, and dried at 80 °C for 12 h to obtain the Pt / UiO-66-NH2 precursor.
[0092] (4) The Pt / UiO-66-NH2 precursor was reduced in a 10 vol% hydrogen-nitrogen mixture at 200 °C for 3 h to obtain Pt / UiO-66-NH2.
[0093] (5) Pt / UiO-66-NH2 was dispersed in 7 mL of ethanol and ultrasonicated for 1 h to obtain a uniform suspension.
[0094] (6) Add ethanol solution of cobalt chloride containing 9 mmol / L of cobalt into the above suspension and stir for 24 h.
[0095] (7) Heat the mixture to 90 °C and stir to evaporate the solvent to obtain a brown solid powder.
[0096] (8) The brown solid powder was reduced in a 10 vol% hydrogen-nitrogen mixture at 200 °C for 3 h to obtain a PtCo / UiO-66-NH2 catalyst with a Co / Pt ratio of 0.2 and a platinum content of 1.5 wt%.
[0097] The PtCo@UiO-66-NH2 bimetallic nanoalloy catalysts obtained in Examples 1 to 4 of the present invention, the Pt@UiO-66-NH2 catalyst obtained in Comparative Example 1, the PtCo(A)@UiO-66-NH2 catalyst obtained in Comparative Example 2, and the PtCo / UiO-66-NH2 catalyst obtained in Comparative Example 3 were subjected to XRD, TEM, XPS, and CO-DRIFT tests, respectively. The results showed that:
[0098] XRD patterns of Examples 1 to 4 of the present invention and Comparative Example 1 without Co ( Figure 1 ) have only the diffraction peak of UiO-66-NH2, and have good crystallinity, without the diffraction peak of Pt nanoparticles and PtCo alloy, indicating that the metal particles are small in size or highly dispersed. However, in the XRD diagram of Comparative Example 2 using cobalt acetate as the cobalt source, the diffraction peak intensity of UiO-66-NH2 is very weak, the peak shape is wide, and the crystallinity is low. Therefore, it can be seen that the PtCo@UiO-66-NH2 prepared by the method of the present invention has a better crystal structure.
[0099] TEM images of Examples 1 to 4 of the present invention ( Figure 2 ) It can be seen that the metal nanoparticles are evenly dispersed throughout the UiO-66-NH2 skeleton structure. As the cobalt content increases, the size of the metal nanoparticles also increases, but the size of the MOFs is relatively consistent, about 300 nm. In Comparative Example 1, the Pt nanoparticles are smaller and evenly dispersed, and the size of the MOFs is 400nm. However, the UiO-66-NH2 particles obtained in Comparative Example 2 are smaller in size and almost fragmented, making it difficult to see the regular structure of MOFs, and the dispersibility of the Pt nanoparticles is also poor. It can be seen from Comparative Example 3 that the Pt nanoparticles enter the UiO-66-NH2 pores, but the particle size is larger and the distribution is uneven. It shows that the PtCo@UiO-66-NH2 prepared by the method of the present invention has a more regular morphology, and Pt is better dispersed.
[0100] Further, the element surface scan was performed according to Example 4 of the present invention ( Figure 3), it can be seen that Co is uniformly dispersed throughout the skeleton, indicating that in addition to forming an alloy with Pt, most of the Co is in the form of Co-N x exists in the form of high-resolution transmission electron microscopy ( Figure 4 ), the lattice fringes d=0.223 nm appear, which is the interplanar spacing of the PtCo alloy, while Comparative Examples 1 to 3 only have interplanar spacings belonging to Pt (111) (d=0.230 nm). This indicates that the PtCo@UiO-66-NH2 prepared by the method of the present invention contains a PtCo bimetallic alloy.
[0101] XPS spectrum ( Figure 5 ) shows that the Pt 4f 5 / 2 The binding energy of Examples 1 to 4 is located at 71.1 eV, which is lower than that of Examples 1 to 4, indicating that the PtCo@UiO-66-NH2 prepared by the method of the present invention forms a Pt δ- In the Co 2p XPS graphs of Examples 3 and 4, the satellite peak at 786.3 eV and the Co 2p at 781.5 eV 3 / 2 The peaks indicate that most of the Co is in the Co-N x Co 2+ In the catalyst of Example 4 with a high cobalt content, the surface Co 0 . It further illustrates that the present invention has both PtCo alloy and CoN in Examples 1 to 4. x sites, all of which are active sites that are favorable for the selective adsorption of C=O bonds.
[0102] The in situ infrared diffuse reflectance spectroscopy of carbon monoxide (CO-DRIFT) also shows that the electronic state of Pt in Examples 1 to 4 of the present invention is effectively regulated ( Figure 6 ). Located at ~2090 cm -1 The CO absorption peak at belongs to Pt δ+ -CO, indicating the presence of Pt-N sites. In addition, with the increase of Co content, the -1 The Pt-CO linear adsorption peak shifts to a lower wavenumber, indicating that the electron density of Pt increases.
[0103] Example 6
[0104] The catalysts of Examples 1 to 5 and Comparative Examples 1 to 3 were used for selective hydrogenation of cinnamaldehyde to test the performance of the catalyst. The reaction was carried out in a 25 ml autoclave, with a catalyst dosage of 10 mg, isopropanol as a solvent, a dosage of 5 mL, and a reactant dosage of 158 mg. The reaction conditions were: H2 2.0 MPa, 70 ° C for 1 h. The composition after the reaction was analyzed by gas chromatography, and n-hexanol was used as an internal standard for quantitative analysis. The test results are listed in Table 1.
[0105] Table 1 Selective hydrogenation performance of cinnamaldehyde
[0106]
[0107] It can be seen from the data in Table 1 that under the same reaction conditions, when cinnamaldehyde is used as the reactant, the reaction results of Examples 1 to 4 are significantly better than those of Comparative Examples 1 to 3, which is mainly attributed to the fact that the PtCo@UiO-66-NH2 nano-alloy catalyst prepared by the method of the present invention has good crystallinity and a large specific surface area, and the Pt nanoparticles, PtCo alloy and Co-N x Multi-site synergistic action of Lewis acids.
[0108] It should be understood that the technical solution of the present invention is not limited to the above-mentioned specific implementation cases. Any technical deformation made according to the technical solution of the present invention without departing from the scope of protection of the purpose of the present invention and the claims shall fall within the protection scope of the present invention.
Claims
1. A method for preparing amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst, characterized in that: The following steps are involved: (1) Dissolving platinum salt and 2-aminoterephthalic acid in N,N-dimethylformamide solvent to form a platinum-containing solution; the molar volume ratio of the platinum salt to the N,N-dimethylformamide is 1 mmol:793 mL; the concentration of the 2-aminoterephthalic acid in the N,N-dimethylformamide is 20 mmol / L; (2) adding acetic acid to the platinum-containing solution and stirring evenly to obtain an acidified platinum solution; the volume ratio of the acetic acid to the N,N-dimethylformamide is 4:23; ⑶ Dissolve the zirconium salt in N,N-dimethylformamide solvent to obtain a mixed solution, add cobalt oxide powder to the mixed solution, stir and ultrasonically disperse for 5 to 30 minutes to obtain a cobalt-containing suspension; the concentration of the zirconium salt in the N,N-dimethylformamide is 80 mmol / L; the mass volume ratio of the cobalt oxide to the mixed solution is 2 to 14 mg: 1 mL; (4) mixing the acidified platinum solution with the cobalt-containing suspension, and transferring the mixture to a reactor with a polytetrafluoroethylene liner for heating reaction to obtain a mixed solution; (5) The mixed solution is centrifuged, washed and dried to obtain a light brown solid product; (6) The solid product is reduced in a hydrogen / nitrogen mixed atmosphere to obtain an amino-functionalized UiO-66-loaded platinum-cobalt bimetallic nanoalloy catalyst PtCo@UiO-66-NH2.
2. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: In the step (1), the platinum salt refers to chloroplatinic acid.
3. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: In step (3), the zirconium salt refers to zirconium tetrachloride or zirconium nitrate.
4. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: In step (3), the cobalt oxide refers to divalent cobalt oxide, i.e., CoO, and the atomic ratio of cobalt to platinum is 0.15 to 1.
1.
5. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: The heating reaction conditions in step (4) are a temperature of 120° C. and a time of 12 to 36 h.
6. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: The washing conditions in step (5) refer to washing with N,N-dimethylformamide and methanol 3 to 4 times respectively.
7. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: The drying conditions in step (5) are a temperature of 80°C and a time of 6 to 12 hours.
8. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: In the step (6), the volume fraction of hydrogen in the hydrogen / nitrogen mixed gas is 10 vol%.
9. The method for preparing the amino-functionalized UiO-66-supported platinum-cobalt bimetallic nano-alloy catalyst according to claim 1, characterized in that: The reduction treatment conditions in step (6) refer to a reduction temperature of 200-250°C and a reduction time of 1-3 h.
Citation Information
Patent Citations
High-dispersion supported PtCo nano-alloy catalyst as well as preparation method and application thereof
CN105148939A
Method for synchronously preparing hierarchical pore cobalt and nitrogen co-doped nanorod loaded platinum-cobalt alloy nano oxygen reduction electrocatalyst
CN111653792A